EXPLORING THE MENTAL ISSUE IN HUMAN BEINGS: A MORAL PERSPECTIVE IN “MEDUSA” BY JESSIE BURTON - Fauzi, Resti Hadiyanti; Pratiwi, Dyani Prades (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2025)
Mental health is a state of well-being that enables individuals to cope with stress, realize potential, learn, work well, and contribute to the community. Jessie Burton's novel "Medusa" depicts Medusa's struggle against trauma and anxiety triggered by a toxic environment, showing the impact of interpersonal relationships on mental health. This research will explore the moral perspectives on mental health issues depicted in "Medusa" and criticize the morality of society through literary representations. The method used in this research is a qualitative method by analyzing data from the novel "Medusa" by Jessie Burton. The theory used is moral criticism. The results of this study show that the novel represented the toxic environment as a critique to society with even showed the effect of it. This study indicates that Medusa's lack of confidence in social interaction and self-acceptance, triggered by fear and isolation, is a major factor in her mental disorder. Toxic environments, such as social pressure and unfair judgment, worsen one's mental health. Medusa's story reveals her trauma, loneliness, and struggle for self-acceptance, as well as the social and moral injustices that exacerbated her suffering. This novel also represented the ideal of the environment as a recommendation and example of the good morality of society should be. Family support and healthy relationships are essential for recovery from trauma and fear. The moral values of the novel include respect for one's personality rather than outward appearance, and the need for empathy and protection regardless of physicality.